Dropout prevention: lessons from a European qualitative research - Mateus, S. (INTED2022 16th annual International Technology, Education and Development Conference, 2022)
Education is crucial to the processes of change and progress in contemporary societies where economic development closely interlinks with knowledge, competences and learning. A growing number of opportunities, whether in the professional, cultural or civic fields, get mediated by the application of competences acquired through academic processes. Such processes have a rising impact on individual biographies. Failing to achieve school success or leaving the education system prior to finishing the basic levels of qualification implies serious consequences in the trajectories of individuals, communities and national economies. The prevention and mitigation strategies against school failure are ever more a local, national and European concern (OECD, 2016a). This presentation discusses the results of a qualitative research on causes and processes of early school leaving, conducted in 2017 in 8 European cities (Amadora/Portugal, Northampton/United Kingdom, Paris/France, Genova and Cuneo/Italy, Osijek and Djal/Croatia, Bucharest/Romania). The research objectives were: a) to give voice to young people's experiences and the process, causes and effects of early school leaving, retention and dropping out; b) to gather a number of "typical histories" of early school leaving or risks of dropping out that reflect the different situations in which ESL occurs; c) to identify the complex factors, actions, and views underlying ESL not only at individual level but also at school and community levels. The following research questions were address empirically: at local level, what are the factors causing school failure, early school leaving and dropping out? How can ESL and dropping out be reduced? Involving young people and conducting a more critical research process led to young people taking on the role of experts as participants. Around 290 young people who have dropped out of school early, or at risk of dropping out, were involved in focus groups and interviews.